Penguatan Budaya Kebersihan di Lingkungan Kampus melalui Edukasi Sanitasi dan Program Pengelolaan Lahan Kosong Berkelanjutan - Uswatun Chasanah; Mohammad Riyan Ammizar; Rahayu Mardikaningsih; Didit Darmawan; Nurul Ilmiyah Al Makrufah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Environmental cleanliness refers to a state in which the environment is protected from pollutants that could compromise health, comfort, and ecosystem sustainability whether in public spaces or on university campuses. In reality, however, many campuses still face cleanliness issues stemming from a lack of awareness regarding hygienic practices. This community service initiative aims to strengthen the culture of cleanliness at Sunan Giri University Surabaya through sanitation education and a sustainable vacant land management program. The project employs the Participatory Action Research (PAR) method, actively involving students, faculty members, and the surrounding community in every stage from planning and implementation to evaluation. Activities included sanitation education, waste collection, weeding, drainage repairs, the painting of campus facilities, and the utilization of vacant land. The results indicate an increase in awareness and participation among the academic community and local residents in maintaining campus cleanliness. Beyond the physical improvements resulting in a cleaner and more orderly environment, the initiative fostered social solidarity and cultivated a sense of collective responsibility for environmental sustainability. Thus, the program contributes positively to establishing a sustainable campus culture of cleanliness that prioritizes environmental health.